Recruitment Strategy Of Teaching Staff And Education Staff In Integrated Islamic Basic Schools Of Cendikia Faiha, Palembang - Maryani (Jurnal Pendidikan Tambusai, 2021)
This study aims to determine the strategy of recruitment of teaching staff and education staff in SDIT Cendikia Faiha Palembang . This research was conducted from July to December 2020, with qualitative research methods and qualitative descriptive research types. Respondents in this study were the head of the foundation as well as the teaching and education staff, including: school principals, curriculum representatives, student representatives, teachers and administrative staff. The writer used observation, interview and documentation techniques to obtain some information. The results of this study are the recruitment of educators and education personnel at SDIT Cendikia Faiha has been going well and effectively. This recruitment activity begins with careful planning in analyzing the needs of educators and education personnel based on the number of students, by a recruitment committee consisting of the head of the Foundation, the principal, the curriculum assistant, the student assistant and some of the teaching staff. Then the stages of vacancy publication to receipt of application documents, procurement of interview test selections, Qur’an recitation / reading Qur’an tests and micro teaching tests as well as a 3-month coaching and orientation process for applicants who pass the selection